Determinants of firm value with profitability as intervening variables - Handayani, Ratih Hapsari; Indarto, Indarto; Santoso, Aprih (Asian Management and Business Review, 2022)
The research objective is to analyze the factors affecting profitability and their impact on firm value of manufacturing companies on the IDX for the 2017-2019 period. Data collection is done by reading secondary data, with the number of companies that match the characteristics of 27 companies, so that the number of samples becomes 81. The analysis method uses SEM-PLS. The research results are asset structure and profitability influence to firm value, while leverage, capital structure, firm size, liquidity, and firm growth have no effect on firm value. The capital structure has an influence to profitability, but leverage, asset structure, firm size, liquidity, and company growth are not having significant results and profitability is not an intervening variable.